Pete the cat's groovy guide to love - Dean, Kim, 1969-; Dean, James, 1957- (New York : HarperCollins, 2015)
A collection of quotes by famous notables, including Vincent van Gogh, Virgil, Ovid, and Charles Dickens, echoes Pete the Cat's thoughts on love.
"Tips from a cool cat on how to spread the love"--Cover.
Keywords: Love -- Juvenile literature; Authors -- Quotations -- Juvenile; Quotations, English; Quotations, American; Love -- Quotations, maxims, etc; Authors -- Quotations; Quotations, English; Quotations, American; Love -- Quotations; Authors -- Quotations; Quotations